191k views
3 votes
Need Help With Functions. Screenshot attatched

Need Help With Functions. Screenshot attatched-example-1
User Delgado
by
5.8k points

1 Answer

6 votes

Answer:

4x² -29x +51

Explanation:

Put x-3 where x is in the original function definition, then "simplify". I think you'll find it convenient to rewrite the original function definition first.

... g(x) = 4x² -5x = x(4x -5)

Substituting, we have

... g(x-3) = (x -3)(4(x -3) -5)

... = (x -3)(4x -17) . . . . . simplify right factor

... = 4x² -12x -17x +51

... g(x -3) = 4x² -29x +51

User Lacop
by
6.6k points